Mechanical and Microstructural Properties of 625 Chromia Forming Alloys in Different Temperatures and Atmospheres - (:unkn) unknown (My University, 2023)
ABSTRACTMECHANICAL AND MICROSTRUCTURAL PROPERTIES OF 625 CHROMIA FORMING ALLOYS IN DIFFERENT TEMPERATURES AND ATMOSPHERES by Davan Jordan Siegfried The University of Wisconsin-Milwaukee, 2023 Under the Supervision of Dr. Benjamin C. Church Inconel alloys have historically been used in high temperature applications because of two significant reasons: high strength at elevated temperatures and excellent corrosion resistance especially in high temperature applications. The resistivity to chemical attack comes from presence of chromium and molybdenum in the alloy (22 and 9 wt%, respectively) and the formation of chromia on the surface when exposed to oxidizing environments. The formation of chromia on the surface does come at a cost to the material. Chromia formation can deplete chromium from the alloy in the region near the surface of the material and is coupled with a reduction of the mechanical properties of the alloy. The objective of this work was to explore the effects of temperature and atmosphere on the bulk and near-surface regions of Inconel 625 and to determine the extent of microstructure and property changes. The samples were chemically tested and compared to the standard chemical composition of Inconel 625 and then tested in three different atmospheres and two different temperatures. The atmospheres were air, air with 10vol% water, and vacuum; temperatures were 650֯C or 750֯C . These conditions are common atmospheres for oxidation tests and the 650-750°C region is where mechanical properties of Inconel 625 begin to decrease significantly. Samples were exposed to the temperature-atmosphere ii conditions for 10 hour increments up to a total of 100 hours. Weight change per unit area was tracked as a function of exposure time. Only the 10-, 30-, and 100- hour samples from each condition were characterized after exposure. After each sample underwent their respective treatment in their environment, they were observed and compared to the as-received sample. Scanning Electron Microscopy (SEM) and Energy Dispersive Spectroscopy (EDS) were used to observe the surface and a cross section of each sample, microhardness and microscopy were also used on the samples cross section. There was a distinct difference that arose when comparing the extremes of the conditions at the surface. This difference was due to the inability to form chromia at the surface in the vacuum sample due to a lack of access to oxygen. The bulk microstructures, however, remained rather similar after exposure to the prolonged atmosphere, where all samples exhibited an increase in the quantity of twinning planes in the matrix. Observing the outer layer of the material there was very little change that occurred at the surface, in terms of chromium migration. This was due to the low temperature ranges used during the experiment. The temperatures used only permitted a maximum potential migration of approximately 6μm using the conditions of 750°C for 100 hours. The microhardness of the bulk material in each sample was dependent solely on the temperature and time of exposure and was completely independent of oxidation atmosphere. The hardness of the material did however correlate with the microstructural changes indicating an increase in twinning translates to a higher hardness in the material. iii After conducting the experiment and observing the results, the next steps would be to elevate the temperature to 850°C, 950°C, and 1050°C to observe other changes that occur that are independent of oxidation.
Keywords: Inconel